The effect of maleic anhydride-grafted polypropylene (MAPP) on properties of paper sludge and kaolin filled polypropylene (PP)/ethylene propylene diene terpolymer (EPDM) hybrid composites / Salmah, H. Ismail and A. Abu Sakar - ., Salmah; Ismail, H.; Abu Sakar, A. (2006)
Polypropylene (PP)/ethylene propylene diene terpolymer (EPDM) hybrid composites were made using kaolin and paper sludge (PS) fillers as reinforcing agents in the PP/EPDM matrix and maleic anhydride-grafted polypropylene (MAPP) was used a compatibilizer. Result indicates that the increasing loading of kaolin in kaolin/paper sludge wt (%) has increased the tensile strength and elongations at break but decrease the Young's modulus and water absorption of PP/EPDM/Kaolin/PS hybrid composites. The presence of MAPP has improved the mechanical properties (such as tensile strength and elongation at break) but reduced the water absorption of PP/EPDM/Kaolin/PS hybrid composites. This observation was due to improvement in the wetting of filler surface and better filler matrix interaction of hybrid composites as evidenced from scanning electron microscopy studies.